Why Well-Being as an Educational Aim Constrains Paternalism in Schools - Krepski, Heather (Philosophical Inquiry in Education, 2025)
In this paper, I aim to showcase and texture the reasons why children’s autonomy is a topic worth revisiting in schools. I advance the premise that student autonomy is a necessary condition for well-being and argue that children’s capacities for autonomy are as broad and important as adult capacities and requirements for autonomy. New understandings about the purpose of school education and what it means to be a child yield important implications for, and constraints on, adult entitlements to paternalizing children in schools. In this paper, I outline reasons why, all things considered, a soft-paternalism approach in schools promotes greater student well-being. I offer practical pathways for teachers to take a soft-paternalism approach that views children as powerful thinkers in school classrooms. The takeaway from this view is that children are entitled to determine their own learning and educational goods for well-being to a far greater degree than is currently promoted in schools.